The Influence of College Physical Education on Students' Psychological Quality from the perspective of Curriculum Ideology and Politics - Jianyun Li, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
With the shift in educational philosophy, college physical education is evolving from a purely biological approach to a holistic, three-dimensional concept that integrates biology, psychology, and social factors. Therefore, college physical education should adopt a dynamic, comprehensive, and developmental approach that considers not only students' physical well-being but also their psychological and social needs. This study examines how college physical education supports student mental health, addressing both theoretical frameworks and curriculum design perspectives. In 2021, 50 students (29 males, 21 females) and 48 students (28 males, 20 females) were selected for the experimental and control groups, respectively. The experimental group participated in outdoor training sessions, while the control group received tennis lessons with similar characteristics to outdoor activities. This study employed a range of research methods, including literature review, questionnaires, statistical analysis, expert interviews, and testing. The investigation explored the historical and conceptual basis of physical education, its current state in terms of student mental and physical health, and the distinctions between outdoor and traditional indoor physical education approaches. The study found that outdoor training positively impacted students’ physical fitness and mental health. The teaching experiment demonstrated that outdoor physical education contributed more effectively to both physical performance and mental well-being than traditional physical training alone. Outdoor physical education is more effective than traditional training methods in enhancing students' physical and mental abilities. While sports are primarily a form of physical exercise, the process significantly influences students' physiological and psychological well-being. Regular physical activity strengthens the body and provides an outlet for negative emotions, helping to relieve tension and depression and foster emotional stability and self-confidence. Thus, teachers should design open, student-centered physical education programs that cater to students’ physiological and psychological needs, incorporate activities that students enjoy, and emphasize the enjoyment of physical education. By participating in enjoyable and varied sports activities, students not only build diverse sports skills but also experience a sense of accomplishment and fun, which further supports their mental and emotional health.